2017
DOI: 10.1111/den.12853
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of confocal laser endomicroscopy to diagnose ulcerative colitis‐associated neoplasia

Abstract: Chromoendoscopy, narrow-band imaging (NBI), and confocal laser endomicroscopy (CLE) have been introduced in ulcerative colitis (UC)-associated neoplasia surveillance. We aimed to determine the ability of CLE to differentiate among UC-associated neoplasia (differentiated type or undifferentiated type), sporadic adenoma, and circumscribed regenerative lesions. Of 665 patients with UC, we carried out probe-based CLE (pCLE) on 12 patients with suspected UC-associated neoplasia in addition to magnifying chromoendos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…21 Sensitivity, specificity, and accuracy of a combination of back-to-back orientation of crypts and dark trabecular architecture for UC-associated carcinoma or dysplasia were 100%, 83%, and 92%, respectively. 21 Large-scale studies are needed to further evaluate the clinical impact of the use of CLE during colonoscopy. EC allows ultra-magnified images to be captured during endoscopy and has made possible the diagnosis of living tumor cells in vivo.…”
Section: Discussion Topics Of the Jges Core Sessionsmentioning
confidence: 94%
See 2 more Smart Citations
“…21 Sensitivity, specificity, and accuracy of a combination of back-to-back orientation of crypts and dark trabecular architecture for UC-associated carcinoma or dysplasia were 100%, 83%, and 92%, respectively. 21 Large-scale studies are needed to further evaluate the clinical impact of the use of CLE during colonoscopy. EC allows ultra-magnified images to be captured during endoscopy and has made possible the diagnosis of living tumor cells in vivo.…”
Section: Discussion Topics Of the Jges Core Sessionsmentioning
confidence: 94%
“…CLE is useful for diagnosis of histopathological findings and invasion depth of colorectal tumors . Also, CLE can predict the inflammation activity of ulcerative colitis (UC) . Sensitivity, specificity, and accuracy of a combination of back‐to‐back orientation of crypts and dark trabecular architecture for UC‐associated carcinoma or dysplasia were 100%, 83%, and 92%, respectively .…”
Section: Discussion Topics Of the Jges Core Sessionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also reported that probe-based CLE showed irregular dark nests in jejunal metastasis from cervical cancer, 16 disorganized irregular dark glands in early-stage gastric cancer covered by nontumorous regenerative epithelium or maturated atypical glands found after Helicobacter pylori eradication, 25 and back-to-back orientation of dark crypts in ulcerative colitis-associated differentiated adenocarcinoma and dark trabecular architecture in ulcerative colitis-associated undifferentiated adenocarcinoma. 26 The Miami classification system based on a consensus of probe-based CLE users to standardize categorization of images indicated that all cancers in the esophagus, stomach, colorectum, and biliary duct were characterized by disorganized structures of dark ("nonrefractile") epithelium or cells. 27 Whether the mechanism by which cancerous cells are unenhanced by fluorescein is ascribed to low influx or high efflux is unknown, but this disorganized structure of unenhanced cells is an important hallmark of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…At JDDW 2017 International Session 9, Nagasaka et al . used probe‐based CLE to observe lesions in 12 patients and detected back‐to‐back‐oriented crypts in CC/D, while branching was observed in tubular adenoma . Although the typical findings of CC/D on CLE remain to be explored, this technology may be useful for establishing a new diagnostic strategy based on histological as well as on molecular abnormalities when combined with molecular science.…”
Section: Characterizationmentioning
confidence: 99%